Changes in endotracheal tube cuff pressure with the changes in peak airway pressures during total laparoscopic hysterectomy and pelvic surgeries. A prospective and observational study - Sami Ullah Mujoo; Sifna Tahir; Umera Ikram (Asian Journal of Medical Sciences, 2023)
Background: The abdominal insufflation and changes in endotracheal tube (ETT) cuff pressure due to creation of pneumoperitoneum and changes in patient positioning during laparoscopic abdominal surgeries have not been explored thoroughly. Aims and Objectives: The aim of our study was to see the changes in ETT cuff pressures during creation, maintenance, release of pneumoperitoneum, and during surgical positioning. Materials and Methods: A total of 60 patients were finally taken for study. Written informed consent was taken for participation in the study as well as consent for surgery. Inclusion criteria were patients of age above 30 years, American society of anesthesiology physical status 1 and 2, patients undergoing total laparoscopic hysterectomy requiring trendelenburg positioning. Exclusion criteria were patients with pre-existing pulmonary or cardiac disease, patients with pre-existing vocal cord palsy, goitre or any other airway or thoracic pathology, pregnant or lactating females, BMI more than 25 or <18.5. Changes of cuff and airway pressures before and after abdominal insufflation in supine position and after head-down or head-up positioning were analyzed and compared. Results: Baseline cuff pressure after manual inflation was 28.85±11.4 cm H2O. Significant correlation was observed between change in cuff pressure and increase in peak airway pressure at the end of the surgery (P<0.05). Serial measurements of ETT cuff pressure, peak airway pressure, and ETCO2 were significantly increased compared to baseline (P<0.05). Conclusion: Pneumoperitoneum in Trendelenburg position increases ETT cuff pressure probably due to increase in airway pressure. Therefore, it seems advisable to include routine monitoring of ETT cuff pressure. Objective adjusted measurement of cuff pressure and airway pressures is recommended for such surgeries.